Correlation functional in screened‐exchange density functional theory procedures. Issue 27 (18th July 2017) - Chan, Bun; Kawashima, Yukio; Hirao, Kimihiko
Abstract : In the present study, we have explored several prospects for the further development of screened‐exchange density functional theory (SX‐DFT) procedures. Using the performance of HSE06 as our measure, we find that the use of alternative correlation functionals (as oppose to PBEc in HSE06) also yields adequate results for a diverse set of thermochemical properties. We have further examined the performance of new SX‐DFT procedures (termed HSEB‐type methods) that comprise the HSEx exchange and a (near‐optimal) reparametrized B97c ( c OS, 0  =  c SS, 0  = 1, c OS, 1  = −1.5, c OS, 2  = −0.644, c SS, 1  = −0.5, and c SS, 2  = 1.10) correlation functionals. The different variants of HSEB all perform comparably to or slightly better than the original HSE‐type procedures. These results, together with our fundamental analysis of correlation functionals, point toward various directions for advancing SX‐DFT methods. © 2017 Wiley Periodicals, Inc. Abstract : The HSE procedure using a B97‐type correlation functional to enable further development of screened‐exchange (SX) DFT has been re‐formulated. The new "HSEB‐type" procedures have the following re‐determined B97c parameters: c OS, 0  =  c SS, 0  = 1, c OS, 1  = −1.5, c OS, 2  = −0.644, c SS, 1  = −0.5, and c SS, 2  = 1.10. It is demonstrated that, even with just near‐optimal parametrization, HSEB already performs comparably to or slightly better than HSE for thermochemistry, molecular structure, and semiconductor bandgap.